High-water-stability sodium-ion battery positive electrode material as well as preparation method and application thereof

By doping Li, Ti, and Sn ions into the sodium ion battery positive electrode material and adopting a sintering process, the problem of poor water stability of the layered oxide positive electrode material is solved, and the water stability and electrochemical properties of the material are significantly improved.

CN119461506APending Publication Date: 2025-02-18TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411636776.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing sodium ion battery layered oxide positive electrode materials have the problem of poor water stability, which is prone to absorb water or react with water-oxygen (or carbon dioxide), affecting structural stability and electrochemical properties.

Method used

By mixing sodium, nickel, manganese, tin, lithium and titanium sources and ball milling to uniformity, then sintering 900-1000°C under an air atmosphere, Ni, Ti, Sn co-doped nickel manganese tin was prepared. Base layered oxide positive electrode material.

Benefits of technology

The water stability of the nickel-manganese-tin-based layered oxide positive electrode material is significantly improved, and it can be stored in air with a relative humidity of 45% for 2 months or soaked in water for 1 week, and maintain the original discharge specific capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461506A_ABST
    Figure CN119461506A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode material with high water stability and a preparation method and application thereof, the preparation method comprises the following steps: uniformly mixing a sodium source, a nickel source, a manganese source, a tin source, a lithium source and a titanium source to obtain a first substance; and sintering the first substance in an air atmosphere at 900-1000 DEG C for 1-12 hours, and cooling along with a furnace to obtain the sodium-ion battery positive electrode material with high water stability. The sodium-ion battery positive electrode material with high water stability is a Li, Ti and Sn co-doped nickel-manganese-tin-based layered oxide positive electrode material, and the water stability of the nickel-manganese-tin-based layered oxide positive electrode material is remarkably improved through the co-doping synergistic effect of Li, Ti and Sn; the electrochemical performance of the composite material is not changed after the composite material is stored in air with the relative humidity of 45% for 2 months and even soaked in water for 1 week, and the original specific discharge capacity and cycle stability are still kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and specifically relates to a sodium ion battery positive electrode material with high water stability, and a preparation method and application thereof. Background Art

[0002] The environmental pollution problem caused by excessive use of traditional fossil energy is becoming increasingly serious. This problem can be effectively alleviated by developing green renewable energy and seeking low-cost, large-scale energy storage systems. Lithium-ion batteries (LIBs) gradually began to be commercialized in the early 1990s. They dominate the energy storage industry because of their excellent energy density. However, lithium ore reserves are low and unevenly distributed, and with the continuous development of emerging industries such as electric vehicles, the demand and price of lithium have increased sharply. Compared with lithium resources, sodium resources are widely distributed and cheap, and are expected to replace LIB and become the new leader in the energy storage industry. Layered oxide cathode materials for sodium ion batteries have attracted widespread attention due to their advantages of feasible synthesis, high operating voltage and high theoretical capacity. In addition, if the capacity stability of the half-cell is poor, it will have a great impact on the performance of the full cell when it is subsequently matched with the full cell, causing the life of the full cell to decay seriously.

[0003] However, layered oxides also have the problem of easily absorbing water or reacting with water-oxygen (or carbon dioxide), which affects the stability of the structure and electrochemical performance. This makes layered oxides unable to be stored in the air for a long time, which puts higher requirements on the production and subsequent storage of batteries.

[0004] The literature with Doi number 10.1002 / sstr.202300150 reported that when Na ions were extracted in the air, the layered oxides were prone to undesirable chemical reactions with substances including H2O, CO2, and O2. It is worth noting that in the bulk phase, H2O and CO2 molecules will be embedded in the interior of the TMO2 sheet, rather than just being absorbed on the surface. In addition, O2 will oxidize transition metals in the layered oxides, such as Fe 2+ and Mn 3+ . This oxidation reaction damages the original structure and electrochemical properties of the material. When exposed to air, the layered transition metal oxides undergo oxidation reactions with water molecules, resulting in H / Na exchange and the production of NaOH. To make matters worse, water-soluble carbon dioxide also participates in the H / Na exchange and generates Na2CO2. This process promotes a decrease in the Na ion content and leads to a larger lattice space due to increased repulsion between adjacent oxide layers and framework instability. In addition, the formation of carbonates deteriorates the surface of the material and increases the acidity. In practical applications, these air-induced reactions pose significant challenges to the stability and performance of layered oxides. It can be seen that the layered oxide positive electrode materials for sodium ion batteries in the prior art have the problem of poor water stability. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing a positive electrode material for a sodium ion battery with high water stability.

[0006] Another object of the present invention is to provide a sodium ion battery positive electrode material with high water stability obtained by the above preparation method.

[0007] Another object of the present invention is to provide an application of the above-mentioned high water stability sodium ion battery positive electrode material in a sodium ion battery.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A method for preparing a positive electrode material for a sodium ion battery with high water stability comprises the following steps:

[0010] Step 1, mixing a sodium source, a nickel source, a manganese source, a tin source, a lithium source and a titanium source until uniform, to obtain a first substance, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, tin in the tin source, lithium in the lithium source and titanium in the titanium source is 0.735:0.27:0.64:0.027:1.05x:y, 0.023<x<0.053, 0.01<y<0.04 in terms of the amount of the substances;

[0011] In step 1, x is preferably 0.027 and y is preferably 0.036.

[0012] In step 1, the sodium source is sodium carbonate, the nickel source is nickel oxide, the manganese source is manganese carbonate, the lithium source is lithium carbonate, the titanium source is titanium dioxide, and the tin source is tin dioxide.

[0013] In step 1, a sodium source, a nickel source, a manganese source, a tin source, a lithium source and a titanium source are mixed and ball-milled to be uniform.

[0014] In the above technical solution, the rotation speed of the ball mill is 300 to 1400 rpm, and the ball milling time is 0.5 to 12 hours.

[0015] Step 2: sintering the first substance at 900-1000° C. for 1-12 hours in an air atmosphere, and cooling the furnace to obtain a sodium ion battery positive electrode material with high water stability.

[0016] The high water stability sodium ion battery positive electrode material obtained by the above preparation method.

[0017] Application of the above-mentioned high water stability sodium ion battery positive electrode material in sodium ion batteries.

[0018] A sodium ion battery comprises the sodium ion battery positive electrode material with high water stability.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The high water stability sodium ion battery positive electrode material of the present invention is a Li, Ti, Sn co-doped nickel manganese tin layered oxide positive electrode material. The radius of the doped Li ion is similar to that of the sodium ion, which can improve or inhibit the occurrence of phase change. The radius of the doped Ti ion and Sn ion is larger, which maintains the crystal structure, plays a supporting structure role, and undergoes oxidation reaction with oxygen, inhibits the overflow of oxygen, and reduces the volume change of the material. Through the synergistic effect of Li, Ti, and Sn co-doping, the water stability of the nickel manganese tin layered oxide positive electrode material is significantly improved. After being stored in air with a relative humidity of 45% for 2 months or even immersed in water for 1 week, its electrochemical performance does not change, and the original discharge specific capacity and cycle stability are still maintained. The high water stability sodium ion battery positive electrode material of the present invention has potential application value in sodium ion batteries, especially in aqueous sodium ion batteries with stringent requirements on the water stability of electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD pattern of the high water stability sodium ion battery positive electrode material of Example 1;

[0022] Figure 2 This is an XRD diagram of the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for one month;

[0023] Figure 3 This is an XRD diagram of the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0024] Figure 4 This is the XRD pattern of the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week;

[0025] Figure 5 This is the XRD pattern of the sodium ion battery positive electrode material of Comparative Example 1;

[0026] Figure 6 a is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 at a current density of 0.2C, Figure 6 b is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 at a current density of 0.2C after being placed in air with a relative humidity of 45% for 2 months, Figure 6 c is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week at a current density of 0.2C;

[0027] Figure 7a is a charge and discharge curve of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2C, Figure 7 b is a charge and discharge curve of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 placed in air with a relative humidity of 45% for 2 months at a current density of 0.2C, Figure 7 c is a charge and discharge curve of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week at a current density of 0.2C;

[0028] Figure 8 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 at a current density of 0.2C;

[0029] Fig. 9 A cyclic voltammogram at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0030] Fig.10 The cyclic voltammogram at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week;

[0031] Fig.11 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2C;

[0032] Fig.12 A cyclic voltammogram at a current density of 0.2C of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0033] Fig.13 The cyclic voltammogram at a current density of 0.2C of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week;

[0034] Fig.14 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 at a current density of 0.5C;

[0035] Fig.15 The cyclic voltammogram at a current density of 0.5C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0036] Fig.16The cyclic voltammogram at a current density of 0.5C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week;

[0037] Fig.17 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.5C;

[0038] Fig.18 A cyclic voltammogram at a current density of 0.5C of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0039] Fig.19 The cyclic voltammogram at a current density of 0.5C of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week;

[0040] Fig. 20 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 at a current density of 1C;

[0041] Fig.21 A cyclic voltammogram at 1C current density of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0042] Fig. 22 The cyclic voltammogram at 1C current density of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week;

[0043] Fig.23 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 1C;

[0044] Fig.24 A cyclic voltammogram at 1C current density of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0045] Fig.25 The cyclic voltammogram at 1C current density of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week;

[0046] Fig.26 The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 at different current densities;

[0047] Fig. 27 The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months at different current densities;

[0048] Fig.28 The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week at different current densities;

[0049] Fig.29 The rate performance diagram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at different current densities;

[0050] Fig.30 The figure is a rate performance diagram of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months at different current densities;

[0051] Fig.31 The rate performance diagram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week at different current densities;

[0052] Fig.32 This is a SEM image of the high water stability sodium ion battery positive electrode material prepared in Example 1;

[0053] Fig.33 This is a SEM image of the high water stability sodium ion battery positive electrode material prepared in Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0054] Fig.34 This is a SEM image of the high water stability sodium ion battery positive electrode material prepared in Example 1 after being immersed in deionized water for one week;

[0055] Fig.35 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1;

[0056] Fig.36 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months;

[0057] Fig.37 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1 after being immersed in deionized water for one week;

[0058] Fig.38 a is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at a current density of 0.2C, Fig.38b is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at a current density of 0.2C after being placed in air with a relative humidity of 45% for 2 months, Fig.38 c is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week at a current density of 0.2C;

[0059] Fig.39 a is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 at a current density of 0.2C, Fig.39 b is a charge and discharge curve diagram of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week at a current density of 0.2C;

[0060] Fig.40 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at a current density of 0.2C;

[0061] Fig.41 The cyclic voltammogram at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week;

[0062] Fig.42 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 at a current density of 0.2C;

[0063] Fig.43 A cyclic voltammogram at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week;

[0064] Fig.44 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at a current density of 0.5C;

[0065] Fig.45 A cyclic voltammogram at a current density of 0.5C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being placed in air with a relative humidity of 45% for 2 months;

[0066] Fig.46 The cyclic voltammogram at a current density of 0.5C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week;

[0067] Fig.47 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 at a current density of 0.5C;

[0068] Fig.48 The cyclic voltammogram at a current density of 0.5C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week;

[0069] Fig.49 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at a current density of 1C;

[0070] Fig.50 A cyclic voltammogram at 1C current density of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being placed in air with a relative humidity of 45% for 2 months;

[0071] Fig.51 The cyclic voltammogram at 1C current density of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week;

[0072] Fig.52 The cyclic voltammogram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 at a current density of 1C;

[0073] Fig.53 A cyclic voltammogram at 1C current density of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week;

[0074] Fig.54 The cyclic voltammogram at 1C current density of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being immersed in deionized water for one week;

[0075] Fig.55 The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at different current densities;

[0076] Fig.56 The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at different current densities after being placed in air with a relative humidity of 45% for 2 months;

[0077] Fig.57The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week at different current densities;

[0078] Fig.58 The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 at different current densities;

[0079] Fig.59 The rate performance diagram of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 at different current densities after being placed in air with a relative humidity of 45% for one week;

[0080] Fig.60 The figure is a rate performance diagram at different current densities of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being immersed in deionized water for one week. DETAILED DESCRIPTION

[0081] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0082] The raw material information involved in the following examples is as follows:

[0083] Diaphragm: Whatman glass fiber diaphragm D1823-025;

[0084] Sodium source (Na2CO3) was purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd., and nickel source (NiO), Ti source (TiO2), Sn source (SnO2), manganese source (MnCO3) and lithium source (Li2CO3) were purchased from McLean Reagent.

[0085] The various performance indicators in the following examples are strictly measured using precise instruments or standard test methods:

[0086] The crystal structure (XRD pattern) of the samples was determined by X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA with a 2θ range of 10 to 80°.

[0087] The constant current charge / discharge performance tests (cycle performance and rate performance) were performed by an automatic battery tester system (LandCT2001A, China) at a constant temperature of 25 °C and 2.0-4.3 V.

[0088] The temperature of the deionized water used for immersion in the following examples is 60°C.

[0089] Examples 1 to 3

[0090] A method for preparing a positive electrode material for a sodium ion battery with high water stability comprises the following steps:

[0091] Step 1, mixing a sodium source, a nickel source, a manganese source, a tin source, a lithium source and a titanium source in a ball mill, high-energy ball milling at a speed of 1400 rpm for 2 hours until uniform (the ball milling medium is acetone), and drying in a blast oven at 80° C. for 2 hours to obtain a first substance, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, tin in the tin source, lithium in the lithium source and titanium in the titanium source is X, the sodium source is sodium carbonate, the nickel source is nickel oxide, the manganese source is manganese carbonate, the lithium source is lithium carbonate, the titanium source is titanium dioxide, and the tin source is tin dioxide;

[0092] Step 2, placing the first material in a muffle furnace, heating to 900°C at a rate of 5°C / min in an air atmosphere, sintering at 900°C for 12 hours, and cooling with the furnace to obtain a positive electrode material for a sodium ion battery with high water stability. X is shown in Table 1.

[0093] Table 1

[0094] Example X serial number Example 1 0.735:0.27:0.64:0.027:0.02835:0.036 <![CDATA[Na 0.7 Ni 0.27 Mn 0.64 Sn 0.027 Li 0.027 You 0.036 O2]]> Example 2 0.735:0.27:0.64:0.027:0.03885:0.026 <![CDATA[Na 0.7 Ni 0.27 Mn 0.64 Sn 0.027 Li 0.037 You 0.026 O2]]> Example 3 0.735:0.27:0.64:0.027:0.04935:0.016 <![CDATA[Na 0.7 Ni 0.27 Mn 0.64 Sn 0.027 Li 0.047 You 0.016 O2]]>

[0095] Comparative Example 1

[0096] A sodium ion battery positive electrode material (Na 0.7 Ni 0.297 Mn 0.676 Sn 0.027 O2) preparation method, comprising the following steps:

[0097] Step 1, mixing a sodium source, a nickel source, a manganese source and a tin source, high-energy ball milling at a rotation speed of 1400 rpm for 2 hours until uniform (the ball milling medium is acetone), and drying in a blast oven at 80° C. for 2 hours to obtain a substance A, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source and tin in the tin source is 0.735:0.297:0.676:0.027 in terms of the amount of substance, the sodium source is sodium carbonate, the nickel source is nickel oxide, the manganese source is manganese carbonate, and the tin source is tin dioxide;

[0098] Step 2: Place material A in a muffle furnace, heat it to 900° C. at a rate of 5° C. / min in an air atmosphere, sinter it at 900° C. for 12 hours, and cool it in the furnace to obtain a positive electrode material for a sodium ion battery.

[0099] Examples 4 to 6 and Comparative Example 2

[0100] A sodium ion battery (a button-type half-cell, a sodium ion battery with a diameter of 20 mm and a thickness of 3.2 mm), comprising: a positive electrode, a counter electrode, a reference electrode, a diaphragm and an electrolyte, wherein the counter electrode and the reference electrode are metal sodium sheets, the diaphragm is a Whatman glass fiber diaphragm D1823-025, the electrolyte is a mixture of an electrolyte and a solvent, the electrolyte is NaClO4, and the concentration of the electrolyte in the electrolyte is 1 mol L -1 The solvent is propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate (PC) to fluoroethylene carbonate (FEC) is 95:5 by volume. The method for preparing the positive electrode is as follows: the positive electrode material, the binder solution and the conductive additive (acetylene black) are mixed until uniform to obtain a slurry, the slurry is coated on an aluminum foil, and dried in a vacuum drying oven at 80°C, and cut into a disc with a diameter of 12 mm as the positive electrode using a cutting machine (the loading amount of the positive electrode material on the positive electrode is 0.9 mg cm -2 ), wherein the binder solution is a mixture of polyvinylidene fluoride (PVDF) and N-methylpyrrolidone, and the concentration of polyvinylidene fluoride in the binder solution is 20 mg mL -1 , the ratio of the positive electrode material, polyvinylidene fluoride and the conductive additive (acetylene black) in the binder solution is 8:1:1 by mass, and the positive electrode material is one of the high water stability sodium ion battery positive electrode materials prepared in Examples 1 to 3 and the sodium ion battery positive electrode material prepared in Comparative Example 1 (the sodium ion batteries of Examples 4 to 6 are prepared in sequence from the high water stability sodium ion battery positive electrode materials of Examples 1 to 3, and the sodium ion battery of Comparative Example 2 is prepared from the sodium ion battery positive electrode material of Comparative Example 1). The sodium ion battery is assembled in a circulating argon glove box with a moisture content of less than 0.01 ppm and an oxygen content of less than 0.01 ppm.

[0101] The high water stability sodium ion battery positive electrode material of Example 1 was subjected to a powder X-ray diffraction test. Figure 1 As shown, the diffraction pattern analysis shows that the high water stability sodium ion battery positive electrode material obtained in Example 1 has a P2 phase layered structure.

[0102] The high water stability sodium ion battery positive electrode material of Example 1 was placed in air with a relative humidity of 45% for 1 month and then subjected to a powder X-ray diffraction test. Figure 2 As shown, by analyzing the diffraction pattern, it is proved that the high water stability sodium ion battery positive electrode material of Example 1 is still a P2 phase layered structure after being placed in air with a relative humidity of 45% for 1 month, indicating that being placed in air with a relative humidity of 45% for 1 month has no effect on its structure.

[0103] The high water stability sodium ion battery positive electrode material of Example 1 was placed in air with a relative humidity of 45% for 2 months and then subjected to a powder X-ray diffraction test. Figure 3 As shown, by analyzing the diffraction pattern, it is proved that the high water stability sodium ion battery positive electrode material of Example 1 is still a P2 phase layered structure after being placed in air with a relative humidity of 45% for 2 months, indicating that being placed in air with a relative humidity of 45% for 2 months has no effect on its structure.

[0104] The high water stability sodium ion battery positive electrode material of Example 1 was immersed in deionized water for one week, filtered and dried, and then subjected to a powder X-ray diffraction test. Figure 4 As shown, by analyzing the diffraction pattern, it is proved that the high water stability sodium ion battery positive electrode material of Example 1 is still a P2 phase layered structure after being immersed in deionized water for one week, indicating that immersion in deionized water for one week has no effect on its structure.

[0105] The sodium ion battery positive electrode material of Comparative Example 1 was subjected to a powder X-ray diffraction test. Figure 5 As shown, the diffraction pattern of Comparative Example 1 proves that it has a P2 phase and an O3 phase layered structure. The sodium ion battery positive electrode material of Comparative Example 1 was placed in air with a relative humidity of 45% for 2 months or the sodium ion battery positive electrode material of Comparative Example 1 was immersed in deionized water for one week and then subjected to a powder X-ray diffraction test, and both also had a P2 and O3 phase layered structure.

[0106] Figure 6 a is a charge and discharge curve of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 at a current density of 0.2C. Figure 6 The charge capacity of a is 123mA h / g, and the discharge capacity is 148mAh / g. Figure 6 b is a charge and discharge curve at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months. Figure 6 The charge capacity in b is 135 mA h / g, and the discharge capacity is 145 mA h / g. Figure 6 FIG. 3 is a charge and discharge curve of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week at a current density of 0.2C. Figure 6 The charge capacity of c is 139mA h / g, and the discharge capacity is 144mA h / g.

[0107] Figure 7 a is a charge and discharge curve of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2C. Figure 7 The charge capacity of a is 190mA h / g, and the discharge capacity is 177mA h / g. Figure 7b is a charge and discharge curve diagram of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months at a current density of 0.2C. Figure 7 The charge capacity in b is 147 mA h / g, and the discharge capacity is 151 mA h / g. Figure 7 c is a charge and discharge curve diagram of a sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week at a current density of 0.2C. Figure 7 The charge capacity of c is 123mA h / g, and the discharge capacity is 129mA h / g.

[0108] like Figure 8 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 has an initial discharge capacity of 148 mA h / g at a current density of 0.2C, and a capacity retention rate of 74% after 100 cycles. Fig. 9 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 145 mA h / g at a current density of 0.2C, and a capacity retention rate of 75% after 100 cycles. Fig.10 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week has an initial discharge specific capacity of 144 mA h / g at a current density of 0.2 C, and a capacity retention rate of 74% after 100 cycles.

[0109] like Fig.11 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 has an initial discharge capacity of 177 mA h / g at a current density of 0.2C, and a capacity retention rate of 43% after 100 cycles. Fig.12 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 151 mA h / g at a current density of 0.2C, and a capacity retention rate of 70% after 100 cycles. Fig.13 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week has an initial discharge specific capacity of 129 mA h / g at a current density of 0.2C, and a capacity retention rate of 73% after 100 cycles.

[0110] like Fig.14As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 has an initial discharge capacity of 138 mA h / g at a current density of 0.5 C, and a capacity retention rate of 81% after 100 cycles. Fig.15 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 134 mA h / g at a current density of 0.5C, and a capacity retention rate of 82% after 100 cycles. Fig.16 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week has an initial discharge specific capacity of 135 mA h / g at a current density of 0.5 C, and a capacity retention rate of 80% after 100 cycles.

[0111] like Fig.17 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 has an initial discharge specific capacity of 160 mA h / g at a current density of 0.5C, and a capacity retention rate of 54% after 100 cycles. Fig.18 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 145 mA h / g at a current density of 0.5C, and a capacity retention rate of 73% after 100 cycles. Fig.19 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week has an initial discharge specific capacity of 123 mA h / g at a current density of 0.5 C, and a capacity retention rate of 83% after 100 cycles.

[0112] like Fig. 20 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 has an initial discharge capacity of 136 mA h / g at a current density of 1C, and a capacity retention rate of 80% after 100 cycles. Fig.21 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 135 mA h / g at a current density of 1C, and a capacity retention rate of 86% after 100 cycles. Fig. 22 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week has an initial discharge specific capacity of 137 mA h / g at a current density of 1 C, and a capacity retention rate of 86% after 100 cycles.

[0113] like Fig.23As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 has an initial discharge specific capacity of 159 mA h / g at a current density of 1C, and a capacity retention rate of 57% after 100 cycles. Fig.24 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 130 mA h / g at a current density of 1C, and a capacity retention rate of 83% after 100 cycles. Fig.25 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being immersed in deionized water for one week has an initial discharge specific capacity of 120 mA h / g at a current density of 1C, and a capacity retention rate of 76% after 100 cycles.

[0114] like Fig.26 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 1 has a discharge capacity of 149mA h / g, 144mA h / g, 137mA h / g, 126mA h / g, 112mA h / g and 90mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 134mAh / g, and the reversibility is strong. Fig. 27 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months has a discharge capacity of 145mA h / g, 150mA h / g, 135mA h / g, 130mA h / g, 115mA h / g and 100mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 139mA h / g, and the reversibility is strong. Fig.28 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 1 after soaking in deionized water for one week has a discharge capacity of 148 mA h / g, 151 mA h / g, 136 mAh / g, 127 mA h / g, 117 mA h / g and 103 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 142 mA h / g, and the reversibility is strong.

[0115] like Fig.29As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 1 has a discharge capacity of 174 mA h / g, 144 mA h / g, 131 mA h / g, 118 mA h / g, 97 mA h / g and 73 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When it returns to 0.1C, the discharge capacity is 132 mA h / g, and the reversibility is poor. Fig.30 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months has a discharge capacity of 156mA h / g, 111mA h / g, 104mA h / g, 101mA h / g, 96mA h / g and 88mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When it returns to 0.1C, the discharge capacity is 117mAh / g, and the reversibility is poor. Fig.31 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 1 after soaking in deionized water for one week has a discharge capacity of 150 mAh / g, 120 mA h / g, 114 mA h / g, 107 mA h / g, 101 mA h / g and 96 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When returning to 0.1C, the discharge capacity is 125 mA h / g, and the reversibility is poor.

[0116] The SEM image of the high water stability sodium ion battery positive electrode material prepared in Example 1 is as follows Fig.32 As shown, the SEM image of the high water stability sodium ion battery positive electrode material prepared in Example 1 after being placed in air with a relative humidity of 45% for 2 months is as follows Fig.33 As shown, the SEM image of the high water stability sodium ion battery positive electrode material prepared in Example 1 after being immersed in deionized water for one week is as follows Fig.34 shown. Figure 33-34 The surface of the positive electrode material for sodium ion batteries with medium and high water stability is relatively smooth, and the morphology is similar to Fig.32 The comparison shows that the residual alkali is reduced, so that the discharge specific capacity of the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 1 after being placed in air with a relative humidity of 45% for 2 months and the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 1 after being immersed in deionized water for one week has no attenuation.

[0117] The SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1 is as follows Fig.35 As shown, the SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months is as follows Fig.36As shown, the SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1 after being immersed in deionized water for one week is as follows Fig.37 shown. Figure 36-37 The residual alkali on the surface of the positive electrode material of the sodium ion battery gradually increases, and the morphology is gradually corroded, so that the discharge specific capacity of the sodium ion battery prepared by the positive electrode material of the sodium ion battery of Comparative Example 1 after being placed in air with a relative humidity of 45% for 2 months and the sodium ion battery prepared by the positive electrode material of Comparative Example 1 after being immersed in deionized water for one week are both attenuated.

[0118] Fig.38 a is a charge and discharge curve of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 at a current density of 0.2C. Fig.38 The charge capacity of a is 176mA h / g, and the discharge capacity is 151mAh / g. Fig.38 b is a charge and discharge curve at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being placed in air with a relative humidity of 45% for 2 months. Fig.38 The charge capacity in b is 157 mA h / g, and the discharge capacity is 122 mA h / g. Fig.38 c is a charge and discharge curve at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week. Fig.38 The charge capacity of c is 111mA h / g, and the discharge capacity is 121mA h / g.

[0119] Fig.39 a is a charge and discharge curve of the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 at a current density of 0.2C. Fig.39 The charge capacity of a is 168mA h / g, and the discharge capacity is 157mAh / g. Fig.39 b is a charge and discharge curve at a current density of 0.2C of a sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week. Fig.39 The charge capacity in b is 138 mA h / g, and the discharge capacity is 118 mA h / g.

[0120] like Fig.40 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 has an initial discharge capacity of 151 mA h / g at a current density of 0.2C, and a capacity retention rate of 70% after 100 cycles. Fig.41As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week has an initial discharge specific capacity of 121 mA h / g at a current density of 0.2C, and a capacity retention rate of 81% after 100 cycles.

[0121] like Fig.42 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 has an initial discharge capacity of 157 mA h / g at a current density of 0.2C, and a capacity retention rate of 76% after 100 cycles. Fig.43 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week has an initial discharge specific capacity of 118 mA h / g at a current density of 0.2C, and a capacity retention rate of 81% after 100 cycles.

[0122] like Fig.44 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 has an initial discharge capacity of 124 mA h / g at a current density of 0.5 C, and a capacity retention rate of 74% after 100 cycles. Fig.45 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 117 mA h / g at a current density of 0.5C, and a capacity retention rate of 73% after 100 cycles. Fig.46 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week has an initial discharge specific capacity of 107 mA h / g at a current density of 0.5 C, and a capacity retention rate of 90% after 100 cycles.

[0123] like Fig.47 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 has an initial discharge capacity of 159 mA h / g at a current density of 0.5 C, and a capacity retention rate of 81% after 100 cycles. Fig.48 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week has an initial discharge specific capacity of 114 mA h / g at a current density of 0.5 C, and a capacity retention rate of 85% after 100 cycles.

[0124] like Fig.49As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 has an initial discharge capacity of 114 mA h / g at a current density of 1C, and a capacity retention rate of 78% after 100 cycles. Fig.50 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being placed in air with a relative humidity of 45% for 2 months has an initial discharge specific capacity of 106 mA h / g at a current density of 1C, and a capacity retention rate of 77% after 100 cycles. Fig.51 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 2 after being immersed in deionized water for one week has an initial discharge specific capacity of 110 mA h / g at a current density of 1 C, and a capacity retention rate of 82% after 100 cycles.

[0125] like Fig.52 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 has an initial discharge capacity of 152 mA h / g at a current density of 1C, and a capacity retention rate of 82% after 100 cycles. Fig.53 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week has an initial discharge specific capacity of 109 mA h / g at a current density of 1C, and a capacity retention rate of 87% after 100 cycles. Fig.54 As shown, the sodium ion battery prepared from the high water stability sodium ion battery positive electrode material of Example 3 after being immersed in deionized water for one week has an initial discharge specific capacity of 101 mA h / g at a current density of 1 C, and a capacity retention rate of 89% after 100 cycles.

[0126] like Fig.55 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 2 has a discharge capacity of 151mA h / g, 137mA h / g, 122mA h / g, 113mA h / g, 103mA h / g and 88mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 130mAh / g.

[0127] like Fig.56As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 2 after being placed in air with a relative humidity of 45% for 2 months has a discharge capacity of 142 mA h / g, 119 mA h / g, 107 mA h / g, 97 mA h / g, 88 mA h / g and 77 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 122 mA h / g.

[0128] like Fig.57 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 2 after soaking in deionized water for one week has a discharge capacity of 128 mA h / g, 125 mA h / g, 110 mA h / g, 101 mA h / g, 96 mA h / g and 81 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 119 mA h / g.

[0129] like Fig.58 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 3 has a discharge specific capacity of 170mA h / g, 160mA h / g, 148mA h / g, 140mA h / g, 129mA h / g and 108mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge ratio is 150mA h / g.

[0130] like Fig.59 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 3 after being placed in air with a relative humidity of 45% for one week has a discharge capacity of 115 mA h / g, 116 mA h / g, 104 mA h / g, 100 mA h / g, 92 mA h / g and 79 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 112 mA h / g.

[0131] like Fig.60 As shown, the sodium ion battery prepared by the high water stability sodium ion battery positive electrode material of Example 3 after soaking in deionized water for one week has a discharge capacity of 120mA h / g, 111mA h / g, 103mA h / g, 95mA h / g, 85mA h / g and 72mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When the current density returns to 0.1C, the discharge capacity is 117mA h / g.

[0132] It can be seen from the cyclic voltammogram that the high water stability sodium ion battery positive electrode material prepared in Example 1 is stored in an environment with a certain humidity or immersed in water, and its discharge specific capacity and long cycle performance are basically unchanged, while the long cycle performance of the sodium ion battery positive electrode material prepared in Comparative Example 1 is greatly affected by being stored in an environment with a certain humidity or immersed in water. The discharge specific capacity of Comparative Example 1 is reduced after being placed in the air and immersed in water, and it is difficult to maintain high discharge specific capacity and cycle stability at the same time. Example 1 has both high discharge specific capacity and high cycle stability (capacity retention rate), and has better performance during the use of the battery. Combined with Table 2 (initial discharge specific capacity and capacity retention rate under long cycle), a comparative summary analysis is performed to prove that the water stability performance of the high water stability sodium ion battery positive electrode material co-doped with Li, Ti, and Sn is excellent.

[0133] Table 2

[0134]

[0135]

[0136] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for a sodium ion battery with high water stability, characterized in that: The following steps are involved: Step 1, mixing a sodium source, a nickel source, a manganese source, a tin source, a lithium source and a titanium source until uniform, to obtain a first substance, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, tin in the tin source, lithium in the lithium source and titanium in the titanium source is 0.735:0.27:0.64:0.027:1.05x:y, 0.023<x<0.053, 0.01<y<0.04 in terms of the amount of the substances; Step 2: sintering the first substance at 900-1000° C. for 1-12 hours in an air atmosphere, and cooling the furnace to obtain a sodium ion battery positive electrode material with high water stability.

2. The preparation method according to claim 1, characterized in that: In step 1, a sodium source, a nickel source, a manganese source, a tin source, a lithium source and a titanium source are mixed and ball-milled to be uniform.

3. A sodium ion battery positive electrode material with high water stability obtained by the preparation method according to any one of claims 1 to 2.

4. Use of the high water stability sodium ion battery positive electrode material as claimed in claim 3 in sodium ion batteries.

5. The use according to claim 4, characterized in that: After the high water stability sodium ion battery positive electrode material is stored in air with a relative humidity of 45% for 2 months, the discharge specific capacity of the sodium ion battery prepared therefrom changes by less than 3%.

6. The use according to claim 4, characterized in that: After the high water stability sodium ion battery positive electrode material is stored in air with a relative humidity of 45% for 2 months, the capacity retention rate of the sodium ion battery prepared therefrom decreases by less than 2% after 100 cycles.

7. The use according to claim 4, characterized in that: After the sodium ion battery positive electrode material with high water stability is immersed in water for one week, the discharge specific capacity change of the sodium ion battery prepared therefrom is less than 3%.

8. The use according to claim 4, characterized in that: After the sodium ion battery positive electrode material with high water stability is immersed in water for one week, the capacity retention rate of the sodium ion battery prepared therefrom decreases by less than 2% after 100 cycles.